2018
DOI: 10.1159/000495051
|View full text |Cite
|
Sign up to set email alerts
|

Niacin Inhibits Apoptosis and Rescues Premature Ovarian Failure

Abstract: Background/Aims: Over 99% of mouse and human ovarian follicles will undergo specialized cell death including atresia and apoptosis. Reduction of apoptosis may help reduce infertility and maintain the reproductive ability in women. Methods: 3-day B6D2F1 mice were used to culture small follicle and ovary tissue with niacin and 18-day mice were intraperitoneal injected with niacin to determine its effect on follicle development. Then establish 8-weeks POF animal model with cytoxan (CTX) or radiation. Treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…4-19 times more than other deciduous trees and conifers; Burkholder & McVeigh, 1944). Dietary content in niacin is crucial for mammal reproduction (Mishra, Aderao, Chaudhary, & Raje, 2018;Tissier, Handrich, Dallongeville, Robin, & Habold, 2017;Wang et al, 2018). Deficiencies in this vitamin lead to reproductive failure in another food-hoarding rodent, whereas dietary supplementation in this vitamin led to above-average reproductive rates (Tissier et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…4-19 times more than other deciduous trees and conifers; Burkholder & McVeigh, 1944). Dietary content in niacin is crucial for mammal reproduction (Mishra, Aderao, Chaudhary, & Raje, 2018;Tissier, Handrich, Dallongeville, Robin, & Habold, 2017;Wang et al, 2018). Deficiencies in this vitamin lead to reproductive failure in another food-hoarding rodent, whereas dietary supplementation in this vitamin led to above-average reproductive rates (Tissier et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data highlight that MT1, JNK1, PCNA, and AMPK may participate in cellular proliferation, apoptosis, migration, and ovary damage. Although stem cell therapy restores ovarian function in POI by directly mediating MT1, JNK1, PCNA, and AMPK, which has not been previously reported, a supporting study revealed that melatonin effectively elevated the percentage of PCNA-positive granulosa and theca cells [29] and that the radiation-POF mouse model treated with niacin highly expressed PCNA in the GCs [55]. In a recent study, human ovaries and hGCs were exposed to cisplatin in vitro, which elevated the levels of the phosphorylated forms of SAPK/JNK and triggered apoptosis [56].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to assess the effect of niacin on mammary gland development in pubertal mice. It has also been reported that niacin can promote the proliferation of breast cancer cells and cancer stem cells and promote the development of immature oocytes[19-21]. Compared with other vitamins, vitamin A and vitamin D currently inhibit puberty mammary gland development[10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Niacin promotes the synthesis of growth hormone[17, 18]. In addition, previous studies have shown that niacin can promote the development of immature follicular cells and the proliferation of cancer cells[19-21].…”
Section: Introductionmentioning
confidence: 99%